A Comparative Study on the Dynamic Tensile Strength Evaluation Method of Rock Materials - Se-Wook Oh; Byung-Hee Choi; Yong-Bok Jung; Sang-Ho Cho (Shock and Vibration)
The representative calculation methods of dynamic tensile strength applied to the spalling test are comparatively reviewed in the same experimental cases. The results are compared with those of the ISRM suggested dynamic BD method. Through comparative verification results and analysis of methodological characteristics of each determination method in the spalling test, the most reasonable method for calculating dynamic tensile strength in the high strain rate condition is derived. The local strain rate and apparent strain rate are calculated for the same experimental cases, and the difference in the result values according to the strain rate calculation technique is analyzed through comparative verification of the calculated results. Consequently, the characteristics of each dynamic tensile strength determination method and strain rate calculation method in the spalling test are presented, and the results of the review on the most suitable method for calculating the dynamic tensile strength of rock materials are presented.